Europe's experience: Investing in rural revitalization - Matthews, Alan (International Food Policy Research Institute, 2019)
Rural development is a top priority of the European Union (EU), designated as one of two pillars under the Common Agricultural Policy since 2000. The EU’s multisectoral approach includes a variety of activities described in this chapter. Farmers are provided compensation for adopting sustainable practices, and young farmers are provided with financial incentives to enter and stay in agriculture. Spending on rural and farm diversification, value-added and rural services, and infrastructure is expected to improve rural livelihoods and create rural jobs. Operational groups consisting of farmers, researchers, businesses, and NGOs are given support to work together in developing new products, processes, and technologies. The chapter points to the valuable lessons that Europe’s experience can provide for rural revitalization in developing countries.